Space production and socioespace segregation: an analysis based on the theory of Space Syntax in Santa Cruz do Sul, RS - Bezerra Júnior, Ricardo Barros (2024)
This study investigates socio-spatial patterns on the beaches of Itamaracá, an island located in the Metropolitan Region of Recife (PE). Recognized for its scenic attractions and easy access to the capital, the island played a significant role in tourism, especially between the 1980s and 1990s, with the spread of vacation homes by the metropolitan middle class in its territory. Despite intense real estate-touristic development, studies indicate current tourist evasion, while part of the media perpetuates a negative view of the island. Based on this debate, the research aims to deepen the understanding of the current panorama of Itamaracá Island through a socio-spatial study, relying on the Theory of Social Logic of Space (Syntax) and census data from IBGE for the year 2010, considering variables such as income and population density. The study revealed complexities in the territory and the distribution of different social groups on the island. Proximity to the sea distinguishes the wealthier, who are divided in a duality of logics: some prefer areas of high accessibility, prioritizing access to services, while others seek greater seclusion through a process of voluntary segregation. Poor neighborhoods tend to be located in the interior of the territory.